Issues Of Digitalization And Automation Of Accounting In Budgetary Organizations - Farmonkulova, Zulkhumor Sobirovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article covers the theoretical and practical aspects of digitalization and automation of accounting in budgetary organizations. The impact of the process of introducing digital technologies on the accounting system, their role in increasing the accuracy and reliability of financial information is analyzed. The importance of automated accounting systems in the effective use of budget funds, strengthening financial control and making management decisions is also substantiated.